Single-graded CIGS with narrow bandgap for tandem solar cells. Issue 1 (31st December 2018) - Feurer, Thomas; Bissig, Benjamin; Weiss, Thomas P.; Carron, Romain; Avancini, Enrico; Löckinger, Johannes; Buecheler, Stephan; Tiwari, Ayodhya N.
Abstract: Multi-junction solar cells show the highest photovoltaic energy conversion efficiencies, but the current technologies based on wafers and epitaxial growth of multiple layers are very costly. Therefore, there is a high interest in realizing multi-junction tandem devices based on cost-effective thin film technologies. While the efficiency of such devices has been limited so far because of the rather low efficiency of semitransparent wide bandgap top cells, the recent rise of wide bandgap perovskite solar cells has inspired the development of new thin film tandem solar devices. In order to realize monolithic, and therefore current-matched thin film tandem solar cells, a bottom cell with narrow bandgap (~1 eV) and high efficiency is necessary. In this work, we present Cu(In, Ga)Se2 with a bandgap of 1.00 eV and a maximum power conversion efficiency of 16.1%. This is achieved by implementing a gallium grading towards the back contact into a CuInSe2 base material. We show that this modification significantly improves the open circuit voltage but does not reduce the spectral response range of these devices. Therefore, efficient cells with narrow bandgap absorbers are obtained, yielding the high current density necessary for thin film multi-junction solar cells. Abstract :